2022
DOI: 10.3390/nu14102022
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo Biloba Leaf Extract Improves an Innate Immune Response of Peripheral Blood Leukocytes of Alzheimer’s Disease Patients

Abstract: Background: One of the main features of Alzheimer's disease (AD) pathology is failure in innate immune response and chronic inflammation. Lack of effective AD treatment means that more attention is paid to alternative therapy and drugs of natural origin, such as extract of Ginkgo biloba (EGb). The purpose of this study was to investigate the effect of EGb on the mechanisms of innate immune response of peripheral blood leukocytes (PBLs) in AD patients. Methods: In AD patients and healthy-age matched controls, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“… Primary bioactive compounds in Ginkgo biloba and their pharmacological effects (created with BioRender using information from [ 21 , 22 ]). Up and down arrows indicate the upregulation and downregulation of relevant biomarkers, respectively.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“… Primary bioactive compounds in Ginkgo biloba and their pharmacological effects (created with BioRender using information from [ 21 , 22 ]). Up and down arrows indicate the upregulation and downregulation of relevant biomarkers, respectively.…”
Section: Figurementioning
confidence: 99%
“…It has been shown that EGb 761, a standardized extract that contains bilobalide, 24% flavone glycosides (quercetin, kaempferol, and isorhamnetin), and 6% terpenes, increases the synthesis of INF-γ, while reducing the release of pro-inflammatory cytokines in peripheral blood leukocytes [ 22 ]. Docking simulations and inhibition kinetic studies have demonstrated that ginkgolic acids and bioflavonoids derived from Ginkgo biloba exhibit comparatively potent SARS-CoV-2 3CLpro inhibitory capabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies on the influence of ginkgo on the functioning of the nervous system, mainly ginkgo leaf extracts were used [ 3 , 140 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 ], less often tablets [ 176 , 177 ]. The use of all these types of preparations was conducive to the reduction of inflammatory processes within the nervous system [ 128 , 170 ], the number of nerve cells subject to damage and apoptosis [ 169 , 173 ] and the improvement of blood circulation within the cerebral vessels [ 171 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…In a Phase II study, a significant drug-placebo difference in the ADAS-Cog12 favoring GV-971 was present [ 172 ]. Ginkgo Biloba has been related to an anti-inflammatory and antioxidant effect [ 173 ]. Furthermore, Ginkgo Biloba manifested a beneficial effect on the circulatory system (blood flow improvement, reduced platelet aggregation, reinforcing the walls of the capillaries), reducing one of the most important comorbidities associated with AD [ 174 ].…”
Section: Inflammation and Admentioning
confidence: 99%